THE RELEVANCE OF DIGITALIZATION OF EDUCATION ON THE EXAMPLE OF SOUTH KOREA - Abdalimova, Darya (MMIT Proceedings, 2023)
The digitalization of education is a process that was given a powerful impetus by the pandemic 2019. The scale of this phenomenon is unlimited, and the stages and forms of implementation differ depending on many factors. The digital environment is becoming an integral part of life, and the adoption of competent and timely digital decisions in the field of education will lead to an increase in its quality level and the opportunities for all segments of the population to have access to education.